1992
DOI: 10.1007/bf00184810
|View full text |Cite
|
Sign up to set email alerts
|

The pharmacokinetics of two different concentrations of short-acting insulin, intermediate-acting insulin, and an insulin mixture following subcutaneous injection

Abstract: To compare the pharmacokinetics of two different concentrations, containing either 40 or 100 IU/ml of short-acting human insulin (Velasulin HM), intermediate-acting human insulin (Insulatard HM), or an insulin mixture (25% short-acting insulin, 75% intermediate-acting insulin; Mixtard HM), three randomized, single-blind, crossover trials were performed using the euglycemic clamp technique. Eighteen healthy volunteers received insulin of either formulation subcutaneously in each of the studies (15 IU Velasulin,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

1993
1993
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…A range of studies have described concentration‐dependent absorption kinetics of subcutaneous bolus injection of human insulin . The different studies concerning human insulin, in different concentrations, showed varying outcomes . Several studies displayed a difference between U40 and U100 human insulin while others failed to do so .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A range of studies have described concentration‐dependent absorption kinetics of subcutaneous bolus injection of human insulin . The different studies concerning human insulin, in different concentrations, showed varying outcomes . Several studies displayed a difference between U40 and U100 human insulin while others failed to do so .…”
Section: Discussionmentioning
confidence: 99%
“…The different studies concerning human insulin, in different concentrations, showed varying outcomes . Several studies displayed a difference between U40 and U100 human insulin while others failed to do so . One of them showed a small but significant difference after 1.5 h, and another showed an initial difference, whereas two studies showed significance at 30 and 45 min after injection .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…between 10 and 5000 IU/ml [5] slower absorption of more concentrated insulin was most clearly demonstrated. Reports concerning differences in pharmacokinetic properties between 40 IU/ml insulin (U40) and 100 IU/ml (U100) have been inconsistent, mainly due to small sample sizes [6][7][8]. The following study assesses the impact of a 2.5-fold increase from U40-to U100-insulin on insulin absorption from the subcutaneous depot, as well as confounding anthropometric variables in a large sample of healthy subjects.…”
mentioning
confidence: 99%
“…Differences between NPH and Regular insulin pharmacokinetics and pharmacodynamics are well-known (14,(16)(17)(18). Mixtures of these two insulins have also been studied, but such studies have generally been limited to 70/30 or mixtures with greater percentages of NPH insulin (18,19). Distinct differences in the serum concentration versus time curves were found between the two mixtures (Fig.…”
Section: Discussionmentioning
confidence: 92%